Profile of the understanding of pre-service physics teacher students on free body diagrams - Yudi Guntara; Deni Aryati (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
This study aims to determine: (1) The ability of free diagram representation student objects on Newton's Law material (2) Student difficulties in represents a free-body diagram on Newton's Law material. The type of research that carried out is a mix method research. The research was conducted through written test activities and Interview. Test activities are used to obtain data on the ability to represent diagrams object-free, namely in the form of a free-body diagram. Interview activities are used to obtaining data on student difficulties in describing object-free diagrams in the form of a description of the results of the interview. The research subjects were students in the Department of Physics Education UNTIRTA and students majoring in Physics Education UNSIQ. The results showed that the student's object-free diagram representation ability included in the category of Needs Improvement (needs improvement). The most difficulty Many students experience in making free-body diagrams is determining the length of the vector forces acting on objects.